THE INFLUENCE OF SUPERVISION AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE WITH COMPETENCY AS AN INTERVENING VARIABLE AT THE MEDAN RELIGIOUS TRAINING CENTER - Sudiro, Sudiro; Farida Ferine, Kiki (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2023)
Human resource management (HRM) is a science or method of how to manage the relationships and roles of human resources efficiently and effectively and can be used optimally so as to achieve the goals of the company, employees and society to the fullest. This study aims to see the Effect of Supervision and Work Discipline on Employee Performance with Competence as an intervening variable with an associative quantitative research type. This research was conducted at the Medan Religious Education and Training Center. research by distributing questionnaires and primary data sources are also used. The research model uses path analysis and the measurement tool uses Smart PLS 3.3.3. The results of this study are as follows: Work discipline has a positive and significant effect on employee performance. Work Discipline has a positive and significant effect on competence. Competence has a positive and significant effect on Employee Performance. Supervision has a positive and significant effect on Employee Performance. Supervision has a positive and significant effect on competence. Work Discipline has a positive and significant effect on Employee Performance through Competence. Supervision has no significant positive effect on Employee Performance through Competence.